2019
DOI: 10.1088/1742-6596/1363/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Lecture Scheduling System Using Welch Powell Graph Coloring Algorithm in Informatics Engineering Departement of Universitas Malikussaleh

Abstract: Scheduling lectures is a routine work in the academic system in higher education every time to facing a new semester. In the implementation, often the schedule that has been issued has not been fixed so it requires to rescheduling. For this reason, a new lecture scheduling system is needed using the Welch Powell Graph Coloring Algorithm. This study was done in the Informatics Engineering Departement of Universitas Malikussaleh using the subjects schedule during 2013, 2014 and 2015. Based on the results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Abdullah et al, [45] presented the Welch Powell Graph Colouring Algorithm to develop an efficient lecture scheduling system. The study demonstrated using multiple years of datasets from Universitas Malikussaleh concluded that it successfully resolves lecture scheduling problems by preventing scheduling conflicts.…”
Section: Heuristicmentioning
confidence: 99%
“…Abdullah et al, [45] presented the Welch Powell Graph Colouring Algorithm to develop an efficient lecture scheduling system. The study demonstrated using multiple years of datasets from Universitas Malikussaleh concluded that it successfully resolves lecture scheduling problems by preventing scheduling conflicts.…”
Section: Heuristicmentioning
confidence: 99%
“…The Greddy algorithm includes the Welch Powell algorithm (Lewis, 2021) and (Hazizah et al, 2023), when the Kruskal's Hendra Cipta, Rina Widyasari, Fikri Husin Batubara algorithm and the Prims algorithm are available in addition to the Welch Powell algorithm (Cipta & Widyasari, 2020). The steps for coloring using the Welch Powell algorithm are as follows (Ganguli & Roy, 2017) and (Abdullah et al, 2019):…”
Section: Coloring Graph Algorithmmentioning
confidence: 99%
“…Besides that, there are several other studies that have been conducted by researchers including, research Lecture Scheduling System Using Welch Powell Graph Coloring Algorithm in Informatics Engineering Departement of Universitas Malikussaleh (Abdullah et al, 2019), Mixed integer linear programming model for integrated fish supply chain planning (Nurdin et al, 2020), Robust optimization approach for agricultural commodity supply chain planning , Data Driven Optimization Approach to Fish Resources Supply Chain Planning in Aceh Province (Nurdin et al, 2019) Optimization and Computing Model of Fish Resource Supply Chain Distribution Network and Implementation of the BFS algorithm and web scraping techniques for online shop detection in Indonesia (Nurdin, Bustami et al, 2021).…”
Section: Introductionmentioning
confidence: 99%